Multilaboratory Evaluation of Disk Diffusion Antimicrobial Susceptibility Testing of Neisseria meningitidis Isolates - Jorgensen, James H. (American Society for Microbiology, 2006)
In 2005, the Clinical and Laboratory Standards Institute published MIC interpretive criteria for 13 antimicrobial agents used for either therapy or prophylaxis of Neisseria meningitidis infections. The MIC method includes the use of lysed horse blood-supplemented Mueller-Hinton broth with incubation in 5% CO(2) for 20 to 24 h. Since some clinical laboratories might prefer the option of disk diffusion testing for infrequently encountered isolates a multicenter collaborative study was conducted to evaluate the reproducibility of a disk diffusion method for testing isolates of N. meningitidis. Interpretive criteria were developed for 12 antimicrobial agents. Four laboratories tested a common collection of 50 meningococcal strains and then tested 25 unique isolates per laboratory. Isolates were tested using Mueller-Hinton sheep blood agar plates incubated for 20 to 24 h in 5% CO(2); they were also tested by the reference broth microdilution method in parallel. Pooling of the MIC and disk diffusion data from the common and unique isolates provided a sufficient sample size to develop susceptible, intermediate, and resistant zone diameter interpretive criteria using the error rate-bounded method for the following agents: chloramphenicol, trimethoprim-sulfamethoxazole, ciprofloxacin, and rifampin. Due to the lack of resistant strains at the present time, “susceptible only” interpretive criteria were proposed for cefotaxime, ceftriaxone, meropenem, azithromycin, and minocycline. The numbers of minor interpretive errors with penicillin and ampicillin disk tests were unacceptably high and precluded recommended testing of those agents by the disk method. However, amdinocillin, an agent that preferentially binds to the altered penicillin binding protein responsible for diminished penicillin susceptibility, has potential utility as a surrogate screening reagent for ampicillin resistance. A disk diffusion breakpoint was derived for nalidixic acid to serve as a surrogate marker for gyrase A mutations associated with diminished fluoroquinolone susceptibility. Disk diffusion testing with meningococci can be performed in a reproducible manner with several antimicrobial agents and represents a practical and cost-effective option for testing sporadic clinical isolates or for surveillance purposes by resource-limited laboratories.